Konstruksi Sosial Identitas Gender dalam Kehidupan Rumah Tangga Masyarakat Sidodadi, Sidoarjo - Fitri, Rahma Safitriana (Journal of Politics and Democracy, 2025)
This study examines the social construction of gender roles in the Sidodadi community, Sidoarjo Regency, emphasizing the tension between traditional norms and ongoing social changes. Using a qualitative approach through in-depth interviews and participatory observation, the research analyzes how social interactions shape and maintain gender identity, drawing on Berger’s social construction theory. The findings show that although women increasingly participate in education and the workforce, traditional norms continue to strongly influence the division of domestic tasks and authority in family decision-making. However, among younger families there is a tendency toward more egalitarian relations, particularly due to greater access for women to education and employment. These results confirm that gender identity is not merely determined by biological factors but is instead a product of social interactions legitimized by traditions and local institutions. This research contributes to gender studies in Indonesia by providing new insights into the dynamics of gender roles at the community level in rural areas and offering a basis for policies that promote gender equality.